Dual Nature of Neutrophil Extracellular Traps (NETs)—From Cancer’s Ally to Therapeutic Target - Karolina Buszka; Claudia Dompe; Kinga Derwich; Izabela Pieścikowska; Michał Nowicki; Joanna Budna-Tukan (Cells)
Cancer remains a major global health challenge requiring the development of diagnostic and therapeutic strategies. Liquid biopsy is considered a promising minimally invasive tool for cancer screening, prognosis and treatment monitoring. Recent studies suggest that neutrophil extracellular traps (NETs) may also be potential liquid biopsy markers. NETs are web-like chromatin structures released by neutrophils in response to various stimuli to trap and neutralize pathogens. However, excessive or dysregulated NET formation has been implicated in tumor progression and metastasis. Elevated levels of NETs have been observed in patients with various types of cancer and correlate with disease stage and prognosis. The presence of NET markers such as citrullinated histone H3 (H3Cit), neutrophil elastase (NE) and myeloperoxidase (MPO) has been associated with higher tumor burden and poorer clinical outcomes. Several studies have shown a positive correlation between NET markers and circulating free DNA (cfDNA) levels, suggesting that NETs may increase the sensitivity of liquid biopsy in detecting and monitoring cancer progression. This review examines the role of NETs in the tumor microenvironment, their contribution to cancer progression and metastasis, and their potential use in liquid biopsy and cancer therapy.